SISTEM PAKAR UNTUK DIAGNOSA PENYAKIT NYERI AKUT MENGGUNAKAN METODE CERTAINTY FACTOR DAN FORWARD CHAINING BERBASIS WEB - Wayan Andre Pratama; I Made Gede Sunarya; I Nengah Eka Mertayasa (Universitas Pendidikan Ganesha, 2022)
Acute pain has been recorded as the most comman complaint which brings patients to the hospital. Acute pain that is not treated early on a proper and sustainable basis can be at risk of becoming chronic pain. The limited number of health workers makes the health services process on handling acute pain earlier become harder to do. This triggers people's habits to prefer to do self-medication. However, this habit is not well supported by the fact that Indonesian people's knowledge of using drugs is still low to moderate. It can increase the possibility of medication errors such as increasing drug side effects. In the management of acute pain, a consultant who can diagnose the type of acute pain disease is needed. In this research, an expert system was built to diagnose types of acute pain that experienced by patients, as well as provided solutions for each type of acute pain disease. The method used in this expert system is a combination of Certainty Factor and Forward Chaining methods. The combination of these two methods was chosen because it is suitable in the process of identifying the type of acute pain, and the result of applying this method is a percentage. This system was built using the Waterfall method with stages starting from the analysis, design, implementation, testing, and maintenance stages. Based on the stages that have been carried out, this system has been successfully built very well, it could be seen from the BlackBox and Whitebox software tests with a 100% success rate. The accuracy testing of the system diagnoses results against expert diagnoses involving 20 test cases obtained a 100% conformity level, which means this system could be used to diagnose the acute pain diseases very well.